Technical-economic analysis of sheep and goat herds in Romania - Irina-Adriana Chiurciu; Elena Cofas (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper aims to identify the number of sheep and goats existing in Romania, spread over Macroregions, Development Regions and counties and to present its evolution in the period 2014-2019. At the same time, a comparison will be made with the situation registered in 1990. The favorable conditions for raising sheep and goats have placed Romania on the 3rd place in the European Union in terms of their number. In 2019, the number of sheep meant 10,358,699 heads, and those of goats 1,594,862 heads. These values increased compared to 2014 by 8.83% for sheep and 12.54% for goats. At the level of Macroregions, most sheep were found in Macroregion One - 4,095,872 heads, representing 40% of the total, and in Macroregion Two, most heads of goats - 664,473 heads, representing 42% of the total, valid values for the year 2019. The development regions where most animals were registered were N-W Region - 2,285,787 for sheep and S-E Region 425,834 for goats. It should also be mentioned that Timi÷s County - 612,638 sheep heads and Constan÷ta County - 140,559 goat heads, were on the first places at NUTS 3 level, in the breeders' ranking. All these results conclude that in Romania the high growth potential of sheep and goats is not exploited, an occupation that could represent an advantage for the relaunch of the livestock sector.
Keywords: Q10; 330; goats; herds; livestock; sheep; Romania